2018
DOI: 10.1089/lap.2018.0393
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y Gastric Bypass: Surgical Technique and Tips for Success

Abstract: Obesity is a worldwide increasing concern, and its prevalence has risen rapidly over the past several decades. Since nonsurgical treatment for weight loss in morbidly obese patients has poor long-term outcomes, bariatric surgery has gained acceptance and popularity in the last years. The laparoscopic Roux-en-Y gastric bypass has proved to be safe and effective, with successful long-term outcomes in morbidly obese patients. Key elements for the success of the operation are careful patient selection, a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…BS aims at reducing body weight and improving health of patients with class 2 or higher obesity. 14 The most commonly applied techniques are the RYGB and sleeve gastrectomy (SG). In the former, most of the stomach is bypassed by creating a small gastric pouch (6 to 8 cm in length and 4 to 6 cm in width).…”
Section: Bariatric Surgery: Procedures and Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…BS aims at reducing body weight and improving health of patients with class 2 or higher obesity. 14 The most commonly applied techniques are the RYGB and sleeve gastrectomy (SG). In the former, most of the stomach is bypassed by creating a small gastric pouch (6 to 8 cm in length and 4 to 6 cm in width).…”
Section: Bariatric Surgery: Procedures and Mechanismsmentioning
confidence: 99%
“…A gastrojejunostomy is performed, obtaining the alimentary limb, whereas the gastric remnant forms the proximal end of the biliary limb and is connected by jejunojejunostomy, thus forming the common limb. 14,15 The exact limb length differs slightly by technique and center preference, with the alimentary limb measuring 100 to 150 cm and the biliary limb measuring 70 to 150 cm. 14 SG, on the other hand, implies the resection of the greater gastric curvature, leaving a narrow gastric tube along the lesser curvature, accounting for 10% of the stomach volume.…”
Section: Bariatric Surgery: Procedures and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…HTN, T2DM, and dyslipidemia were also significantly improved after LRYGBP. [131][132][133][134] LRYGBPprocedures are minimally invasive procedures that are safe, feasible, and preferred over open RYGBP because of the short hospital stay and low perioperative morbidity. Additionally, weight loss after five years of LRYGBP is markedly improved; a study showed that, in a 5-year period, of the 1160 patients who had a LRYGBP, 240 had T2DM or impaired fasting glucose.…”
Section: Lrygbp Proceduresmentioning
confidence: 99%